Consumer Protection Of Credit Card Using Customers According To Law Number 8 Of 1999 - Jessica Aydaputri Masloman (Estudiante Law Journal, 2019)
The purpose of this study is to determine the legal protection of credit card customers according to Law Number 8 of 1999. The type of research used is empirical legal research. While the sampling used purposive sampling and data analysis using a qualitative research approach. The results show that the times have changed society in conducting transactions, one of which is transactions using credit cards. According to research, the low level of customer knowledge regarding the use of credit cards has caused many customers to suffer losses, ranging from telephone fraud, terror committed by debt collectors, to data leaks by customers. Thus, the legal protection provided to protect customers is protection before the transaction and after the transaction. In addition to Bank Indonesia, Bank Indonesia also pprotectsby issuing a Government Regulation for the operation of card-based payment instruments, other forms of protection are stated in the UUPK Article 45 Paragraph 1 and Paragraph 2. In addition, if there is a loss to the rights of the customer, the bank will also be responsible. by providing compensation, if it is proven that the bank made a mistake.